2019
DOI: 10.1093/gbe/evz055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Reveals the Genetic Mechanisms of Musk Secretion and Adaptive Immunity in Chinese Forest Musk Deer

Abstract: The Chinese forest musk deer ( Moschus berezovskii ; FMD) is an artiodactyl mammal and is both economically valuable and highly endangered. To investigate the genetic mechanisms of musk secretion and adaptive immunity in FMD, we compared its genome to nine other artiodactyl genomes. Comparative genomics demonstrated that eight positively selected genes (PSGs) in FMD were annotated in three KEGG pathways that were related to metabolic and synthetic activity of musk, similar to previous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…However, Moschidea is a sister group of Bovidae or of Cervidae, has obtained different results in different analyses [28,[31][32][33][34]. Previous studies on phylogenetic analysis based on whole-genome sequences revealed that forest musk deer as more closely related to Bovidae than to Cervidae, which is consistent with the results of the present study [35,36,76]. Historically, the fossil records and some molecular phylogenetic studies regarded Siberian musk deer WSMD as the primitive species in Moschus [25,37,38].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, Moschidea is a sister group of Bovidae or of Cervidae, has obtained different results in different analyses [28,[31][32][33][34]. Previous studies on phylogenetic analysis based on whole-genome sequences revealed that forest musk deer as more closely related to Bovidae than to Cervidae, which is consistent with the results of the present study [35,36,76]. Historically, the fossil records and some molecular phylogenetic studies regarded Siberian musk deer WSMD as the primitive species in Moschus [25,37,38].…”
Section: Discussionsupporting
confidence: 84%
“…These categories seem to be help musk deer living at high altitudes avoid high levels of ultraviolet radiation and forage in darkness. The previous study based on the forest musk genome has identified eight PSGs genes enriched in the phototransduction pathway and retinol metabolism pathways [35]. Our results and theirs did not have overlap candidate genes.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations